The Beginnings of the Organisation of Polish Historical Science in Great Britain after World War II - Zuziak, Janusz (Faces of War, 2024)
After the defeat of September 1939, a large number of Polish historians found themselves, together with the army, scattered abroad. They lost their previous academic research base, aids and equipment, book collections, notes, etc. As early as the autumn of 1939, the first attempts to organise representatives of this group were made in allied France. The fall of France and the necessity to evacuate to Great Britain meant that a new stage of wartime activity began here for the Polish civilian and military leadership, the organisation of the army and the organisation of the community of Polish historians. The first institutions were established soon after arrival in the United Kingdom. After the end of the war, a number of Polish historians decided to remain abroad and the process of establishing academic institutions began, giving rise to Polish historical science in the UK. The General Sikorski Historical Institute was the first institution to be established, and other institutions soon followed, including the Piłsudski Institute in London, the Polish Underground Movement Study Trust, the Polish Historical Society in Great Britain, the Polish University Abroad, and the Polish Library.